Linking knowledge to action: the role of boundary spanners in translating ecology - Safford, Hugh D; Sawyer, Sarah C; Kocher, Susan D; Hiers, J Kevin; Cross, Molly (Frontiers in ecology and the environment, 2017)
One of the most effective ways to foster the co-production of ecological knowledge by producers and users, as well as encouraging dialogue between them, is to cultivate individuals or organizations working at and managing the boundary between the two groups. Such "boundary spanners" are critical to ensuring scientific salience, credibility, and legitimacy, yet they remain relatively underused in ecology. We summarize some of the major roles of boundary spanners in translational ecology, and suggest that effectiveness in translating ecological information depends on several key factors. These include organizational and individual commitment to boundary spanning over the long term; development of useful, co-produced products and tools that can subsequently assume boundary-spanning roles of their own; dual-accountability frameworks that involve both science providers and users; and identification, training, and retention of science translators who possess a suite of professional skills and individual traits that are rare in scientific circles.